Rachel Kyte visits the Nyando Climate Smart Villages - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Rachel Kyte, the CGIAR Fund Council Chair and World Bank Vice President for Sustainable Development (right) visited the Nyando Climate Smart Villages in Kenya on 8th November 2013. This is a collection of photos from the visit. Photos: S. Kilungu (CCAFS)